PENGEMBANGAN ALAT PERAGA PEMBELAJARAN MATEMATIKA MATERI PERKALIAN BERBASIS MONTESSORI: INDONESIA - Apri Wahyudi; Choirudin (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2019)
AbstractThis study aims to develop a learning tool to determine the results of multiplication of students to create alearning process that will be more interesting and fun. With the existence of Montessori teaching aids,this will improve the quality of the school and will be more advanced in the teaching and learningprocess. This study uses the Research and Development (R & D) method that produces a product, andtests the effectiveness of the product. From the results of the validation by material experts, mediaexperts, mathematicians can be seen, the results of the validation of the material experts fall into the veryfeasible category. And screening trials by teachers and students fall into the category of proper use.AbstrakPenelitian ini bertujuan untuk mengembangkan alat peraga motessori menentukan hasil Perkalian siswauntuk mencipkatan proses pembelajaran akan menjadi lebih menarik dan menyenangkan. Dengan adanyaalat peraga Montessori ini akan meningkatkan kualitas sekolah dan akan lebih maju lagi dalam prosesbelajar mengajar. Penelitian ini menggunakan metode Reseach and Development (R&D) yangmenghasilkan suatu produk, serta menguji keefektifan produk tersebut. Dari hasil validasi oleh ahlimateri, ahli media, ahli matematika dapat diketahui, hasil validasi terhadap ahli materi masuk dalamkategori sangat layak. Dan ujicoba pemkaian oleh guru dan siswa masuk dalam kategori layak digunakan